Hybrid precoding method for millimeter-wave massive MIMO systems based on IAFS algorithm - Haoyi CHEN; Guangqiu LI; Hui LI (Dianxin kexue)
The millimeter-wave massive multiple-input multiple-output (MIMO) systems can overcome the adverse effects of the free-space signal path loss through the partial connection hybrid precoding method, which has the advantages of low hardware complexity and high energy efficiency.When the number of input data streams is equal to the number of radio frequency (RF) links, the hybrid precoding method based on partially connected structure and serial interference cancellation can be used.When the number of input data streams is not equal to the number of RF links, a hybrid precoding method based on improved artificial fish swarm (IAFS) algorithm was proposed.The core idea is that based on the spectral efficiency optimization criteria and the characteristics of partial connected structure, the spectral efficiency optimization problem of analog recoding matrix variables was transformed into the spectral efficiency optimization problem based on vector variables, and then the IAFS algorithm was used to solve the spectrum efficiency optimization problem.The simulation results show that the proposed method has good spectral efficiency and energy efficiency under the condition of low signal-to-noise ratio, and is expected to be applied in the real scene.